2019
DOI: 10.1111/head.13607
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Management of Headache after Pediatric Emergency Department Visit: Are we Missing Anything?

Abstract: Background Headache is a common complaint in children at a pediatric emergency department (PED). The primary objective of this analysis is to describe the outcome of patients presenting with headache to the PED and discharged with neurology follow up. The secondary objective is to describe the diagnostic evaluation children with headache underwent in the PED and to evaluate headache characteristics which are more likely associated with serious, life‐threatening conditions. Methods A retrospective chart review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 18 publications
1
9
0
1
Order By: Relevance
“…Diffuse headache, vomiting, visual disturbances, pupillary abnormalities, nocturnal awakening with headache, strabismus, nystagmus, ataxia, paresthesia, cranial nerve palsy, weakness, altered mental status, speech difficulty, and meningismus findings were more prevalent in cases of severe headache. The proportion of patients admitted to the PED with symptoms of headache (0.6%) in our series was similar to prior studies, representing a range of 0.6-1.3% of PED visits [1,2,5,6,12,13].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Diffuse headache, vomiting, visual disturbances, pupillary abnormalities, nocturnal awakening with headache, strabismus, nystagmus, ataxia, paresthesia, cranial nerve palsy, weakness, altered mental status, speech difficulty, and meningismus findings were more prevalent in cases of severe headache. The proportion of patients admitted to the PED with symptoms of headache (0.6%) in our series was similar to prior studies, representing a range of 0.6-1.3% of PED visits [1,2,5,6,12,13].…”
Section: Discussionsupporting
confidence: 89%
“…The average age of children with headache was found as 8.8-9.6 years in previous studies [1,2,5,6,8]. Glatstein et al [12] reported that the mean age and median age were 10.2 and 10.4 years, respectively. In our study, the median age was 13.3 years.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations